By the Honourable Robert Hunter Morris, Esq ; lieutenant governor, and commander in chief of the province of Pennsylvania, and counties of New-Castle, Kent and Sussex, upon Delaware, a proclamation. : Whereas the Delaware tribe of Indians, and others, in Confederacy with them, have ... fallen upon this province, and in a most cruel, savage and perfidious manner, killed and butchered great numbers of the inhabitants ... Given under my hand and the great seal of the province, at Philadelphia, the fourteenth day of April ... one thousand seven hundred and fifty-six. . (Printed by B. Franklin, and D. Hall, 1756)
April 14, 1756 Proclamation of Lieutenant Governor Robert Hunter Morris finding the Delaware Tribe of Indians, and others in confederacy with them, to be enemies and traitors as a result of their attacks on inhabitants.